La práctica pedagógica en profesores iniciantes de matemáticas (2022)
Eng: This research presents the analysis of a sample of five beginning teachers’ pedagogical practices graduated from the Bachelor of Mathematics of the Pedagogical and Technological University of Colombia, through a qualitative approach with a case study, with information gathering techniques such as: interview, observation and triangulation. Considering some theoretical references regarding Mathematics Education and Didactics with Rico (1999) and D'Amore (2004), teacher training and practices with Shulman (2005) and Zuluaga (1999), likewise a model of conceptions about mathematics based on the theories of Ponte (1992) and Godino (2004) (idealism, instrumentalism, constructivism and dynamism). Some results show that according to the conception adopted by the teacher, their actions are reflected in the classroom. Within idealism, it is highlighted that, in mathematics practices, is considered as the set of rules, facts and procedures, in instrumentalism the importance of acquiring some basic algorithms, in constructivism the applicability of mathematics and dynamism with the contextualization of knowledge mathematician in culture and society. In addition, it is considered that the mathematics teachers’ training has a significant impact on practices when the teaching experience is minimal and they adopt some methodologies of their teachers' teachers.